(untitled) (Research, Society and Development, 2022)
Palliative care is used for patients in their treatment or care, which improves or alleviates suffering at a given time, but which is not able to solve the problem or cure an illness. This work aims to analyze studies on the importance of applying palliative care to the elderly in Intensive Care Units (ICU). This is an Integrative Literature Review. The databases were LILACS, SCIELO and BDENF. The articles were with a time frame from 2016 to 2021. In view of the evidence found in the literature, it is also added that palliative care is an approach that improves the quality of life of patients and their families in the face of a disease that puts them at risk the continuity of life, through prevention and relief of suffering, involving early identification. However, some problems surround this issue, in which the vast majority of palliative practices are aimed at cancer patients. Nursing professionals assume responsibilities with elderly patients and their families until it is possible to maintain quality of life, starting from physical care with daily meals to hygiene, in addition to psychological and emotional support.